2002
DOI: 10.1021/om010913h
|View full text |Cite
|
Sign up to set email alerts
|

Multiple C−H Bond Activation. Threefold-Deprotonated 6-Phenyl-2,2‘-bipyridine as a Bridging Ligand in Dinuclear Platinum(II) Derivatives

Abstract: Unusual platinum(II) trimetalated derivatives have been synthesized and characterized by reaction of cis-[Pt(R) 2 (DMSO) 2 ] (R ) Me, Ph) and 6-phenyl-2,2′bipyridine. The behavior of the substituted 2,2′-bipyridine as a threefold-deprotonated ligand is unprecedented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 18 publications
3
41
0
Order By: Relevance
“…25,27 Gentle heating of the new complexes 5a-c results in a C-H activation reaction of the phenyl ring, similar to that seen before. 26,28,29 Cyclometallated products 6a-c are now seen, presumably accompanied by the elimination of methane, Scheme 4. The platinum bound methyl groups in 6a-c are confirmed to be trans to the NHC ligand via a series of NOE experiments; if we take the R' = Me complex 6a as a representative example, we can see NOE interactions between the Pt-Me and the cyclometallated ring, between the PtMe and the DMSO protons and between the DMSO protons and the R' group (and vice versa, in each case).…”
Section: A-d 2a-dmentioning
confidence: 99%
See 1 more Smart Citation
“…25,27 Gentle heating of the new complexes 5a-c results in a C-H activation reaction of the phenyl ring, similar to that seen before. 26,28,29 Cyclometallated products 6a-c are now seen, presumably accompanied by the elimination of methane, Scheme 4. The platinum bound methyl groups in 6a-c are confirmed to be trans to the NHC ligand via a series of NOE experiments; if we take the R' = Me complex 6a as a representative example, we can see NOE interactions between the Pt-Me and the cyclometallated ring, between the PtMe and the DMSO protons and between the DMSO protons and the R' group (and vice versa, in each case).…”
Section: A-d 2a-dmentioning
confidence: 99%
“…We had hoped that we could induce one or both of the complexes 3 or 4 to undergo a cyclometallation reaction, but we were unable to find suitable conditions and reagents to facilitate such transformations. The reagent PtMe 2 (DMSO) 2 has been reported 26 to induce facile cyclometallation reactions and we thus tried it. Reaction of the silver NHC complexes 2 with PtMe 2 (DMSO) 2 has not previously been documented, but we can report that it works well as another method of selectively introducing a single NHC ligand to a platinum(II) centre, giving excellent yields, Scheme 3.…”
Section: Br -mentioning
confidence: 99%
“…[1,2] Having the same shape and electronic configuration as 2,2′:6′,2′′-terpyridine (terpy), [3] the (Phbpy) -anion provides very stable tridentate binding and the cyclometalation, requiring C-H activation of the phenyl core, can be carried out at moderate conditions, usually by heating suitable Pt II or Pd II precursors and the C-H functionalised protoligands (ligand precursors, prior to metalation). [1,2,[4][5][6][7][8][9][10][11][12][13][14] Very soon after their initial use, it was found that many Pt II derivatives of the Phbpy ligand show intense luminescence, some even at ambient temperature. [11,[15][16][17][18][19] One reason lies in the destabilisation of dark metal-centred excited states associ-to 0.44 in PMMA matrices.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the lower electrophilicity of platinum(II) compared to palladium(II) facilitates oxidative addition as an alternative pathway. Thus, for electron-rich platinum precursors such as [PtMe 2 (dmso) 2 ] [31][32][33][34][35][36] or dimer [Pt 2 Me 4 (μ-SMe 2 ) 2 ] [37][38][39][40][41][42][43], the initial coordination of the ligand is followed by a cyclometallation step which, in this case, consists on oxidative addition followed by reductive elimination of methane. As shown in Scheme 1, in addition to formation of cyclometallated platinum(II) compounds, dimethylplatinum precursors allow formation of stable cyclometallated platinum(IV) compounds arising from intramolecular activation of C-X bonds (X = Cl, Br) [41][42][43] of adequately designed ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Although, diphenylplatinum(II) derivatives are reported to be less prone to cyclometallation than the corresponding dimethyl derivatives, metallation of 2-phenylpyridines, benzo[h]quinoline or imines containing biphenyl, pyridyl or pyrimidine fragments has been achieved [44][45][46][47][48]. In addition, "rollover" cyclometallation of substituted bipyridines, including multiple C-H bond activation, and functionalized N-(2'-pyridyl)-7-azaindolyl ligands has been achieved using diarylplatinum precursors (see Scheme 2) [31][32][33]49,50]. Scheme 2.…”
Section: Introductionmentioning
confidence: 99%